Transformation of Settlement Patterns and Spatial Structure in Kampung Melayu Tuatunu, Pangkalpinang - Putra, Hadi Jaya; Mahendra, Fasha Nurliansyah (Journal of Architectural Research and Design Studies, 2025)
Kampung Melayu Tuatunu in Pangkalpinang, Indonesia, presents an insightful case of evolving settlement patterns, transitioning from a colonial-era linear layout to a contemporary combination pattern shaped by Islamic traditions and modern urbanization. This study traces the historical development of these spatial patterns, highlighting the pivotal role of Masjid Raya Tuatunu as both a physical anchor and a symbol of the community's socio-cultural identity. Utilizing historical maps, Google Earth imagery, and field observations, the research reveals how colonial road networks gave rise to linear settlements that have gradually transformed into a combination pattern that integrates Malay-Islamic heritage with urban development, illustrating the community’s delicate balance between tradition and modernity. The findings offer insights relevant to urban sociology, Southeast Asian studies, and urban development. Keywords: Colonial Influence; Kampung Melayu; Settlement Patterns; Tuatunu; Urban Development